2009
DOI: 10.1258/jtt.2009.003011
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes to telemedicine among doctors and patients in India

Abstract: We collected information about awareness and attitudes to telemedicine from 143 doctors at 14 different hospitals in India, and from 121 patients who had come to New Delhi for treatment from other parts of India. Most doctors felt that telemedicine was important and their opinions were similar in all age groups. Only three of the 14 hospitals had not implemented telemedicine. A total of 86 doctors had used telemedicine. One hundred of the 121 patients were not aware of telemedicine. However, when the concept w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…Further research could objectively study the impact of successful connected health-related implementations on patient, provider, and economic outcomes [13,14,25]. Hospital training programs for all doctors, as well as awareness programs for patients, are required to stimulate future eHealth and telemedicine utilization [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Further research could objectively study the impact of successful connected health-related implementations on patient, provider, and economic outcomes [13,14,25]. Hospital training programs for all doctors, as well as awareness programs for patients, are required to stimulate future eHealth and telemedicine utilization [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In an another study by Meher, the results showed that medical practitioners were more willing to use telemedicine services and in order to improve the acceptance of telemedicine, educational programs and access to more remote areas are necessary. On the other hand 80% of the Indian patients were unaware of telemedicine services which are especially important due to scope and population of India ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study by Sorensen titled “Attitudes toward telehealth use among rural residents: a Danish survey” showed that the attitude toward new technologies were generally negative in these areas which presented challenges for introducing telemedicine services in these areas ( 8 ). Also the results of n study my Meher et.al on the awareness and attitudes of Indian medical practitioners and patients regarding telemedicine showed the necessity of educational programs in order to change the attitude of both patients and doctors and implement telemedicine ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can impede the effectiveness of health information delivered by technologies. However, as studies have shown, the willingness and confidence to use telemedical systems does not significantly differ when comparing rural and urban populations [11], showing that the path for telemedical systems in healthcare can be made once sufficient education is provided and awareness granted [21].…”
Section: Specifics Of Rural Healthcarementioning
confidence: 99%